Improving The Fifth Grade Students’ Vocabulary Achievement Through Song Integrated With Picture - Roudlotun Nurul Laili; Muhammad Nashir (Educatio, 2018)
Vocabulary as one of language components becomes a vital part in mastering language, especially English as a foreign language. Without having sufficient vocabularies, it is impossible for students to be able to communicate and use language well. Song which is integrated with picture is believed to be able to enlarge the students’ vocabulary mastery since both song and picture can acquire students’ curiosity and attention and able to encourage them to enjoy learning. This research was carried out to improve the fifth grade students’ vocabulary achievement through song integrated with picture at MI UNGGULAN AL ISHLAH Tembokrejo - Muncar - Banyuwangi. The research design applied was a classroom action research (CAR) in collaboration with an English teacher which was conducted in two cycles. The data was collected from interview, observation and test. The research result revealed that there is an improvement on the students’ vocabulary test and their active involvement during learning process in cycle 1 and 2. The mean score of vocabulary test increased from 69.9 in cycle 1 to 76.38 in cycle 2 and more than 75% of the students involved actively in the vocabulary teaching learning process in cycle 2. It met the target criteria of success which means that song which is integrated with picture can enlarge students’ vocabulary achievement and make students more enthusiastic in classroom.